Juridical Review of Consumer Change in the Form of Donations - Afifah Ananda Nafirah; Tiara Reva Oktaviarni; Mutiara Sistriyani; Rahman Rahman; Agus Dimyati (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
The customer refund system at minimarkets like Alfamart has drawn criticism for creating an imbalance between consumers and pelaku usaha. Although Law No. 8 of 1999 on Consumer Protection grants consumers equal legal standing with pelaku usaha, practical issues persist, particularly regarding consumer rights when insufficient uang kembalian is provided. This research examines the legal protections for consumers who incur losses due to a lack of uang kembalian at Alfamart and explores available legal remedies. Using a descriptive analysis approach with a normatif yuridis method, the study evaluates the relevant business law frameworks. Findings reveal that Law No. 8 of 1999 does not specifically regulate insufficient uang kembalian in retail, but the Kitab Undang-Undang Hukum Perdata (Civil Code) classifies failure to provide refunds as wanprestasi (breach of contract). Additionally, pelaku usaha are subject to the principle of strict liability (tanggung jawab mutlak), making them accountable for consumer losses resulting from unlawful acts, regardless of fault. These results highlight the need for clearer legal guidelines on consumer refunds in the retail sector. The study suggests that stricter enforcement of consumer rights and more explicit regulatory frameworks are essential to ensure fair treatment for consumers in retail transactions.